2019
DOI: 10.5419/bjpg2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Granite Waste on the Rheological Behavior of Oil Well Cement Slurries

Abstract: Several materials have been added to oil well cement slurries to improve their fresh and hardened properties. Many of these materials are industrial and agroindustrial wastes, and their use promotes sustainable development, avoiding their disposal in the environment. In this context, this study evaluates the rheological behaviour of oil well cement slurries containing granite cutting waste. The slurries were formulated with additions of 10%, 15%, and 20% of granite waste (by weight of cement-BWOC), as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The possibility of reducing the oil-well cementing cost by replacing the silica flour with the inexpensive granite waste material for applications of cementing the oil-wells hightemperature conditions was evaluated. Three concentrations of the granite waste material (30,35, and 40% BWOC) were evaluated to be used as alternative for 35% silica flour. Based on the evaluated properties and the obtained results, the following points are concluded:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of reducing the oil-well cementing cost by replacing the silica flour with the inexpensive granite waste material for applications of cementing the oil-wells hightemperature conditions was evaluated. Three concentrations of the granite waste material (30,35, and 40% BWOC) were evaluated to be used as alternative for 35% silica flour. Based on the evaluated properties and the obtained results, the following points are concluded:…”
Section: Discussionmentioning
confidence: 99%
“…The use of granite waste in oil-well cementing was suggested by Moura et al 35 The effect of different concentrations of the granite waste material (10, 15, and 20%) on the rheology of the cement under two temperature conditions of 80 and 102 °F was investigated. As an outcome, they concluded that the rheological properties of the cement including up to 20% of granite waste was acceptable.…”
Section: Introductionmentioning
confidence: 99%